Impact of stress and decision fatigue on parenting practices related to food and physical activity during COVID‐19. (14th September 2022) - Angoff, Harrison D.; Dial, Lauren A.; State, Fresno; Varga, Aniko V.; Kamath, Sneha; Musher‐Eizenman, Dara
Abstract: Background: The COVID‐19 pandemic has resulted in substantial disruptions to daily functioning and lifestyle behaviours, with negative health consequences for youth. Parents play a large role in their children's health behaviour; yet changes to parenting behaviours during the pandemic related to food and physical activity remain relatively unexplored. The present study is the first to our knowledge to examine specific changes in American parents' parenting behaviours related to food and physical activity during COVID‐19, and potential correlates of such changes, including perceived stress and decision fatigue. Methods: A total of 140 parents (88.57% female; 88.41% White; 87.59% married; with one to five children) from middle to upper income households completed an online survey assessing demographics, perceived stress (Perceived Stress Scale), decision fatigue (Decision Fatigue Scale) and food and activity parenting behaviour changes during COVID‐19. Results: Overall, a greater proportion of parents engaged primarily in positive (57.14%) than negative (22.86%) parenting practices related to food and physical activity during the pandemic. Moderation analyses showed that the negative relation between perceived stress and positive parental behaviour changes was stronger at higher perceived increases in decision fatigue during the pandemic. Conclusions: In the face of a major public health crisis, adaptive parental responses may emerge, but perceived stress may inhibit such behaviour change. Perceived stress and decision fatigue may represent important explanatory factors in parental health promoting behaviours during times of uncertainty and change.